Microstructure analysis of an as - serviced first stage land based gas turbine blade - Akkoyun, Mehmet Güçl. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2016., 2016)
Superalloys are high temperature materials, and they are used in many industries. Gas turbine industry, aircrafts, and space vehicles are the important industries in which superalloys are used. They are preferred because of their superior properties like high temperature strength, good ductility, and high creep resistance. IN738LC is a polycrystalline nickel base superalloy which is widely used in land based gas turbines. It has a good creep strength and hot corrosion resistance. In this study, a polycrystalline IN738LC turbine blade which has worked 80000 hours at the first stage of the hot section in an electricity producing natural gas turbine is analyzed. Specimens from the root, middle, and tip sections both on the suction and pressure sides of the blade are extracted in order to analyze the grain size and morphology variations in macro scale, and the precipitate size and morphology variations in nano scale. As a result, high/low stress/temperature regions are estimated by using these data. Analysis shows that the base metal of the blade is coated firstly by a NiCoCrAlY layer, then a NiCrAlY layer. The final layer is a thermal barrier coating. Grain size in the cold surfaces is larger than that in the hot surfaces. Since the grain growth is aided by temperature, a larger grain size is expected in the hot surfaces. This seemingly contradictory result is attributed to recrystallization in hot surfaces. Precipitate size in the hot surfaces is larger than that in the cold surfaces. Raft formation is observed in both the suction and pressure sides of the middle and trailing edge positions, and in the stagnation point in the tip section. In the middle section, raft is observed in both the suction and pressure sides of the leading edge and middle positions, and in the stagnation point. Precipitate size in the root section is smaller than that in the middle and tip sections. Very fine precipitates have been observed in cold surfaces of the root section.
Keywords: Gas-turbines.